What’s for dinner today? : Remarks on the provisions and diet of Roman soldiers during the Principate - Tomas, Agnieszka (Instytut Historyczny Uniwersytetu Wrocławskiego, 2020)
Many ancient writers have written about feeding the Roman army, including Vegetius, Appian,Cassius Dio, Tacitus and Suetonius. Archaeological sources provide interesting data about army provisioning,food supply, the soldier's diet, but also the consequences of eating certain types of foods. Analyzing the remainsof consumption and waste, we can reconstruct the diet of soldiers in various corners of the empire and look attheir everyday life "from the kitchen". This contribution is an attempt at an introduction on the nature of literaryand archaeological sources concerning the food supply and diet of soldiers stationed in several selected places inthe empire.